Inflammation and frailty in the elderly: A systematic review and meta-analysis - Soysal, Pinar; Stubbs, Brendon; Lucato, Paola; Luchini, Claudio; Solmi, Marco; Peluso, Roberto; Sergi, Giuseppe; Isik, Ahmet Turan; Manzato, Enzo; Maggi, Stefania; Maggio, Marcello; Prina, A. Matthew; et al. (Ageing research reviews, 2016)
•The pathogenesis of frailty is poorly understood.•Frailty and pre-frailty are associated with higher CRP and IL 6.•Inflammatory parameters are not able to predict the onset of frailty. The pathogenesis of frailty and the role of inflammation is poorly understood. We examined the evidence considering the relationship between inflammation and frailty through a systematic review and meta-analysis. A systematic literature search of papers providing data on inflammatory biomarkers and frailty was carried out in major electronic databases from inception until May 2016. From 1856 initial hits, 35 studies (32 cross-sectional studies n=3232 frail, n=11,483 pre-frail and n=8522 robust, and 563 pre-frail+robust; 3 longitudinal studies n=3402 participants without frailty at baseline) were meta-analyzed. Cross-sectional studies reported that compared to 6757 robust participants, both 1698 frail (SMD=1.00, 95%CI: 0.40–1.61) and 8568 pre-frail (SMD=0.33, 95%CI: 0.04–0.62) participants had significantly higher levels of C-reactive protein (CRP). Frailty (n=1057; SMD=1.12, 95%CI: 0.27–2.13) and pre-frailty (n=4467; SMD=0.56, 95%CI: 0.00–1.11) were associated with higher serum levels of interleukin-6 compared to people who were robust (n=2392). Frailty and pre-frailty were also significantly associated with elevated white blood cell and fibrinogen levels. In three longitudinal studies, higher serum CRP (OR=1.06, 95%CI: 0.78–1.44,) and IL-6 (OR=1.19, 95%CI: 0.87–1.62) were not associated with frailty. In conclusion, frailty and pre-frailty are associated with higher inflammatory parameters and in particular CRP and IL-6. Further longitudinal studies are needed.